Evaluation of antibacterial activity and innate immune components in skin mucus of Indian major carp, Cirrhinus mrigala. (24th September 2015) - Nigam, Ashwini Kumar; Kumari, Usha; Mittal, Swati; Mittal, Ajay Kumar
Abstract: The present work has been undertaken to analyse the antibacterial activity and innate immune components in the skin mucus of Indian major carp, Cirrhinus mrigala . Skin mucus was extracted separately in triple‐distilled water (TDW), 3% acetic acid (3% AA) or 0.1% trifluoroacetic acid (1% TFA). All mucus extracts exhibited different spectrum of the antibacterial activity against different groups of pathogenic bacteria. Protein profiling by polyacrylamide gel electrophoresis revealed a series of protein bands in the TDW extract, four major protein bands in the AA extract and two protein bands in the TFA extract. Tandem mass spectrometry analysis of distinct protein bands identified potential innate immune factors – histone H2A, histone H3, histone H4, haemoglobin, cofilin and nucleoside diphosphate kinase in the TDW extract, and ubiquitin and histone H2B isoforms in acidic extracts of skin mucus of C. mrigala . The presence of these innate immune molecules suggests that skin mucus play an important role in the protection of the fish against microbial invasion.